Financial Efficiency: An Analysis of Accounting Recording Systems in Food Sector MSMEs - Jayusman, Sri Fitria; Harahap, Wilda Sri Munawaroh; Lubis, Reza Hanafi; Hidayat, Toni; Sari, Prista Purnama (International Journal of Economics Development Research (IJEDR), 2025)
Accounting is a systematic process of recording, classifying, simplifying, and communicating financial transaction data with the aim of producing appropriate and reliable information for economic decision-making. In today's modern era, many micro, small, and medium enterprises (MSMEs), which are the backbone of the Indonesian economy, have yet to optimally implement accounting practices. A lack of understanding of accounting, limited human resources, and minimal access to information are the main challenges in implementing accounting in the MSME sector. This study aims to examine the extent of understanding and application of accounting records in 30 MSMEs in Cikondang Hamlet, RT 006/RW 002, located around the Pamulihan Grand Mosque. The data used consisted of primary data obtained through direct interviews with business owners, as well as secondary data sourced from documentation and other references. This study used a descriptive quantitative approach. The results of the study indicate that most MSMEs have not formally implemented accounting principles and still rely on simple records, or do not keep records at all. This has an impact on the inaccuracy of the financial reports produced and hinders accurate business decision-making.